Assessment of depression, malnutrition and co-morbidities of geriatric individuals in rural areas of Bangladesh - Begum, Mst. Umme Hafsa; Islam, Md. Nazrul; Akter, Afsana; Akter, Lima; Akter, Mst. Trisha; Hasnat, Md. Abul; Rabeya, Mst. Rokshana (Intelektual Pustaka Media Utama, 2025)
In rural Bangladesh, elderly populations face distinct health challenges, with depression, malnutrition, and co-morbidities significantly impacting their well-being. This cross-sectional study evaluated 384 older adults across four divisions of Bangladesh using the geriatric depression scale (GDS-15), mini nutritional assessment (MNA), and Katz Index of activities of daily living (ADL). Depression was found among 62.8% of respondents. About 13.0% of participants were malnourished, and 51.8% were at risk of malnutrition. Self reported hypertension (47.1%), arthritis (46.4%), dental problems (43.5%), and insomnia (37.0%) were profound among respondents. The risk of dementia, anorexia, cardiovascular disease, and hypertension was higher among males than females. Geriatric depression was significantly higher in the elderly who were residing in a nuclear family than their counterparts (AOR = 2.114; 95% CI = 1.328-3.365). Additionally, being unemployed was identified as an independent predictor of GD (AOR = 1.992, 95% CI: 1.070 3.709, p = .030). The higher prevalence of depression and risk of malnutrition highlight the pressing requirement for well-coordinated and comprehensive healthcare strategies. The development of multifaceted approaches, incorporating mental health services, nutritional interventions, and socioeconomic support, would enhance elders' well-being.